A Study on Indian Financing Sector and Impact of Foreign Direct Investment on It: An examination of the effects of foreign direct investment on the Indian financing sector (Journal of Advances and Scholarly Researches in Allied Education, 2015)
India has growth prospect for finance industry with ahuge number of consumers and other favorable factors. Opposition toliberalizing FDI in this sector raises concerns about employment losses, unfaircompetition resulting in large-scale exit of incumbent domestic finance andinfant industry arguments to protect the organized domestic finance sector thatis at a nascent stage. In 2012 the IndianGovernment approved proposal of 100 percent FDI in finance in India subject tocertain conditions. Though this proposal is being hailed by global finance giants, which  until  now have  been  involved in only wholesale cash and carrydistribution in India and have been longing for entry into the  Indian finance market for years. The proposalhas received vehement opposition from a spectrum of political parties in India,many of them urging for a reversal of the proposal. As a result, the Indiangovernment has stalled the implementation of this proposal which hastemporarily washed off the wishes of the global finance players awaiting a biteof the Indian finance market. This paper attempts to study the present statusof FDI in finance sector in India and the impacts of FDI on various concernedsegments.